2005
DOI: 10.1093/ajcn/82.5.1052
|View full text |Cite
|
Sign up to set email alerts
|

A 4-wk intervention with high intake of carotenoid-rich vegetables and fruit reduces plasma C-reactive protein in healthy, nonsmoking men

Abstract: In healthy, well-nourished, nonsmoking men, 4 wk of low or high intakes of carotenoid-rich vegetables and fruit did not affect markers of immune function. However, a high intake of vegetables and fruit may reduce inflammatory processes, as indicated by the reduction of plasma C-reactive protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
148
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(162 citation statements)
references
References 36 publications
8
148
0
3
Order By: Relevance
“…The ability of fruit and vegetable intake to suppress inflammation may be due to bioactive nutrients found in these foods including folate, flavonoids, and antioxidants (Watzl et al. 2005; García‐Lafuente et al. 2009).…”
Section: Resultsmentioning
confidence: 99%
“…The ability of fruit and vegetable intake to suppress inflammation may be due to bioactive nutrients found in these foods including folate, flavonoids, and antioxidants (Watzl et al. 2005; García‐Lafuente et al. 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Also, there are increasing evidences with respect to the anti-inflammatory properties of fruit intake. Fruit and vitamin C intakes have been inversely associated with lower concentrations of circulating inflammatory markers (Wannamethee et al, 2006), and a high intake of fruit and vegetables for a 4-week period was recently associated with a significant decrease in CRP serum concentrations (Watzl et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a significant relationship between vitamin C or b-carotene and CRP levels has been observed in healthy subjects 94 . Several interventional studies have demonstrated an anti-inflammatory effect of fruit and vegetable or some of their individual compounds [95][96][97] .…”
Section: Fruit and Vegetablesmentioning
confidence: 99%